2017
DOI: 10.4149/bll_2017_130
|View full text |Cite
|
Sign up to set email alerts
|

High serum levels of IGF-I and IGFBP3 may increase comorbidity risk for asthmatic patients

Abstract: Our results indicate that the serum levels of IGF-I and IGFBP3 are significanlty elevated in the asthma group. We assume that current treatment strategies are not really good enough for asthma. We suppose further strategies which are seeking to balance IGF-I and IGFBP3 should be developed for more effective and curative treatment of asthma (Tab. 2, Fig. 2, Ref. 22).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…HDM-mediated induction of Igf1 could be responsible for IGF1R phosphorylation to promote the asthmatic response, and therefore supports why targeting IGF1R with NVP ameliorates HDM-induced asthma. Accordingly, IGF1 was reported to be involved in airway inflammation and remodeling in asthma and increased in serum of asthmatic patients [ 7 , 13 , 14 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…HDM-mediated induction of Igf1 could be responsible for IGF1R phosphorylation to promote the asthmatic response, and therefore supports why targeting IGF1R with NVP ameliorates HDM-induced asthma. Accordingly, IGF1 was reported to be involved in airway inflammation and remodeling in asthma and increased in serum of asthmatic patients [ 7 , 13 , 14 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent case-control study demonstrated that IGF-1 serum was higher in asthmatics than in control subjects. 11 In contrast, IGF-1 serum was positively associated with lung function in two cross-sectional epidemiological studies in adults, mainly in men, 12,13 although the results do not replicate prospectively. 12 And a recent large cross-sectional study in adults in the UK 14 showed that elevated serum IGF-1 concentration was associated with a low risk of asthma and recent wheezing and improved lung function.…”
Section: Discussionmentioning
confidence: 93%
“…In an in vivo study, IGF‐1 promoted airway inflammation by upregulating IGF‐binding protein 3 (IGFBP‐3), which may have profibrotic effects 10 . A recent case‐control study in adults reported that serum IGF‐1 was higher in asthmatics than in control subjects, but these findings should be interpreted cautiously due to the small sample size 11 . In contrast, IGF‐1 serum was positively associated with lung function in two epidemiological studies in adults, 12,13 and a recent large cross‐sectional study in adults in the UK 14 showed that higher serum IGF‐1 levels were associated with low risk of asthma and recent wheezing and improved lung function (FEV 1 and FVC), suggesting a potential beneficial effect of IGF‐1 on asthma and its parameters in adults.…”
Section: Introductionmentioning
confidence: 99%
“…However, a case-control study of 50 participants reported a positive association of serum IGF-1 with asthma. Nevertheless, the study was limited by a small sample size (21). Indeed, IGF-1 may play a crucial role in asthma, especially in airway hyperresponsiveness, airway inflammation, as well as smooth airway hyperplasia.…”
Section: Discussionmentioning
confidence: 99%